Влияние ионов хрома на проростки некоторых видов и сортов растений, используемых в кормопроизводстве Донбасса - Остапко, И.Н. (Промышленная ботаника, 2006)
Response of some plant species and varieties, being used in Donbass fodder production, on bichromate natrium action depending on its concentration and acting duration was studied. It was fixed that the growth of all studied plant sprouts was inhibited by the chrome ions. Its maximum amount accumulated in the root system of sprouts. Indices of plant resistance are calculated and their values being different for studied plant species and varieties. Onobrychis viciifolia Scop. ′Pestchany 1251′ being the most tolerant to chrome ions action.